Medication Adherence and Associated Factors for Children With Tic Disorders in Western China: A Cross-Sectional Survey - Yang, Chunsong; Qin, Wanxiang; Yu, Dan; Li, Jiayuan; Zhang, Lingli (Frontiers in Neurology, 2019)
Background: This study aimed to explore adherence to prescribed medication among children with tic disorders and examine the factors associated. Methods: This was a cross-sectional study in western China, where children with tic disorders were recruited consecutively in 2018. We used the 8-item Morisky Medication Adherence Scale (MMAS-8) to assess adherence. We included sociodemographic data, disease status, medication status, and family conditions as independent variables, and used an ordinal logistic regression model to examine the factors affecting medication adherence. Results: The participant response rate was 96.2%. The majority of participants (77.5%) were male, aged 7.69 ± 2.58 years. In total, 37.7% were newly diagnosed, 46.1% were review patients, and 16.2% were recurrent patients. Only 40.7% of patients showed good adherence (MMAS-8 score, 8). Decreasing quality of life (adjusted odds ratio 0.974) and living in non-rural areas (adjusted odds ratio 2.361) were significant independent determinants of non-adherence. Conclusion: The results suggest that primary healthcare providers in pediatric clinics should focus on medication adherence counselling for children with tic disorders who have a lower quality of life, and live in non-rural areas. Keywords: medication adherence, tic disorders, quality of life, children